Control elements targeting Tgfb3 expression to the palatal epithelium are located intergenically and in introns of the upstream Ift43 gene - Lane, Jamie; Yumoto, Kenji; Pisano, Justin; Azhar, Mohamad; Thomas, Penny S.; Kaartinen, Vesa (Frontiers in Physiology, 2014)
Tgfb3 is strongly and specifically expressed in the epithelial tips of pre-fusion palatal shelves where it plays a critical non-redundant role in palatal fusion in both medial edge epithelial (MEE) cells and in a thin layer of flattened peridermal cells that covers the MEE. It is not known how Tgfb3 expression is regulated in these specific cell types. Using comparative genomics and transgenic reporter assays, we have identified cis-regulatory elements that could control Tgfb3 expression during palatogenesis. Our results show that a 61-kb genomic fragment encompassing the Tgfb3 gene drives remarkably specific reporter expression in the MEE and adjacent periderm. Within this fragment, we identified two small, non-coding, evolutionarily conserved regions in intron 2 of the neighboring Ift43 gene, and a larger region in the intervening sequence between the Ift43 and Tgfb3 genes, each of which could target reporter activity to the tips of pre-fusion/fusing palatal shelves. Identification of the cis-regulatory sequences controlling spatio-temporal Tgfb3 expression in palatal shelves is a key step towards understanding upstream regulation of Tgfb3 expression during palatogenesis and should enable the development of improved tools to investigate palatal epithelial fusion.